Time to treatment disparities in gastric cancer patients in the United States of America: a comprehensive retrospective analysis - Sharan, Seema; Bansal, Shivam; Manaise, Harsheen Kaur; Jimenez, Paola Berrios; Raikot, Swathi R.; Ahmed, Syeda Hoorulain; Popp, Reed; Popp, Kyle; Sukniam, Kulkaew; Kowkabany, Gabrielle; Mubarak, Fatima; Gabriel, Emmanuel (Frontiers in Oncology, 2024)
Introduction: Gastric cancer ranks as the 5th most prevalent cancer and the 4th leading cause of cancer-related deaths worldwide. Various treatment modalities, including surgical resection, chemotherapy, and radiotherapy, are available for gastric cancer patients. However, disparities related to age, sex, race, socioeconomic factors, insurance status, and demographic factors often lead to delayed time to treatment. Methods: In this retrospective study, conducted between 2004 and 2019, we utilized data from the National Cancer Database (NCDB) to investigate the factors contributing to disparities in the time to first treatment, surgery, chemotherapy, and radiotherapy among gastric cancer patients. Our analysis incorporated several variables, and statistical analysis was conducted to provide valuable insights into these disparities. Results: We observed notable disparities in the timing of treatment for various demographic groups, including age, sex, race, insurance status, geographic location, and facility type. These disparities include longer time to treatment in males (32.67 vs 30.75), Native Americans (35.10 vs 31.09 in Asians), low-income patients (32 vs 31.15), patients getting treatment in an academic setting (36.11 vs 29.61 in community setting), significantly longer time to chemotherapy in 70+ age group (51.13 vs 40.38 in <40 y age group), black race (55.81 vs 47.05 in whites), low income people (49.64 vs 46.74), significantly longer time to radiotherapy in females (101.61 vs 79.75), blacks and Asians (109.68 and 113.96 respectively vs 92.68 in Native Americans) etc. There are various other disparities in time to surgery, chemotherapy, and radiotherapy. Conclusions: Understanding these disparities is crucial in developing targeted strategies to improve timely access to appropriate treatments and enhance outcomes for gastric cancer patients. Future research with updated data and prospective study designs can provide a more comprehensive understanding of the factors influencing patient outcomes in gastric cancer.